2022
DOI: 10.7759/cureus.32316
|View full text |Cite
|
Sign up to set email alerts
|

Family, Individual, and Other Risk Factors Contributing to Risk of Substance Abuse in Young Adults: A Narrative Review

Abstract: Substance use disorder and the availability of certain over-the-counter drugs are worldwide issues that affect many individuals, both mentally and physically. As a result, the frequent use of this substance can lead to substance abuse. This phenomenon is also becoming more prevalent with time, and it does not differentiate between genders, ages, races, or religions. This review aimed to provide an overview of studies related to substance abuse, the individuals who tend to abuse these substances, and their risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…16 This demographic of abusers frequently lacked employment, were single, and had not attained a college education, corroborating previous research that identified employment status, marital status, and educational level as significant predictors of substance abuse. 17 A notable factor contributing to the unexpectedly high incidence of benzodiazepine abuse in this study was the implementation of comprehensive urine screening, which corrected approximately 50% of erroneous clinical diagnoses, thereby enhancing the accuracy of epidemiological data. 18 This is in stark contrast to prior studies conducted in Taiwan that predominantly relied on patient or family self-reports, due to limitations in hospitals' substance abuse detection capabilities.…”
Section: Discussionmentioning
confidence: 90%
“…16 This demographic of abusers frequently lacked employment, were single, and had not attained a college education, corroborating previous research that identified employment status, marital status, and educational level as significant predictors of substance abuse. 17 A notable factor contributing to the unexpectedly high incidence of benzodiazepine abuse in this study was the implementation of comprehensive urine screening, which corrected approximately 50% of erroneous clinical diagnoses, thereby enhancing the accuracy of epidemiological data. 18 This is in stark contrast to prior studies conducted in Taiwan that predominantly relied on patient or family self-reports, due to limitations in hospitals' substance abuse detection capabilities.…”
Section: Discussionmentioning
confidence: 90%
“…Heroin addiction is a complex condition influenced by the combination of genetic elements and environmental factors (9). This study highlighted distinct variations in gene expression when analyzing the gene profile associated with heroin.…”
Section: Discussionmentioning
confidence: 95%
“…The findings of the current study suggest that genetic factors significantly influence compliance with MMT, while environmental and behavioral factors, such as family history and heroin dosage, also play key roles. Individuals with a family history of addiction often show more severe opioid dependence symptoms (9). Family-related risk factors, including prenatal exposure to maternal smoking and inadequate care, lower parental education, neglect, and exposure to substance use within the family, contribute to the risk of drug abuse (32).…”
Section: Discussionmentioning
confidence: 99%
“…One previous study investigated the genetic correlation, pleiotropy, and causal relationships between substance use and psychiatric disorder, suggesting that common risk factors such as specific genes and environmental factors may be risk factors that contribute to both substance abuse and mental disorders [ 28 , 29 ]. Many individuals with additional mental health conditions such as anxiety and depression may use substances as self-medication which can make symptoms worse over time and can lead to severe mental illness and cause substance disorders abuse [ 30 ]. Vice versa, substance use and substance use disorder can cause the appearance of other mental disorders due to changes in brain structures and functions [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%